2009
DOI: 10.1002/adfm.200900120
|View full text |Cite
|
Sign up to set email alerts
|

Doping of Conjugated Polythiophenes with Alkyl Silanes

Abstract: A strong modification of the electronic properties of solution‐processable conjugated polythiophenes by self‐assembled silane molecules is reported. Upon bulk doping with hydrolized fluoroalkyl trichlorosilane, the electrical conductivity of ultrathin polythiophene films increases by up to six orders of magnitude, reaching record values for polythiophenes: (1.1 ± 0.1) × 103 S cm−1 for poly(2,5‐bis(3‐tetradecylthiophen ‐2‐yl)thieno[3,2‐b]thiophene) (PBTTT) and 50 ± 20 S cm−1 for poly(3‐hexyl)thiophene (P3HT). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 39 publications
12
127
0
Order By: Relevance
“…It has been reported that the doping level in P3HT can be varied deliberately by changing the exposure time. [17][18][19] The acceptor density ranges between 10 16 -10 17 cm −3 and n i is about 1.6 × 10 4 cm −3 , leading to a predicted maximum depletion depth between 40 and 200 nm. A semiconductor layer thickness of more than 200 nm was chosen, larger than the predicted maximum depletion depth.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the doping level in P3HT can be varied deliberately by changing the exposure time. [17][18][19] The acceptor density ranges between 10 16 -10 17 cm −3 and n i is about 1.6 × 10 4 cm −3 , leading to a predicted maximum depletion depth between 40 and 200 nm. A semiconductor layer thickness of more than 200 nm was chosen, larger than the predicted maximum depletion depth.…”
Section: Resultsmentioning
confidence: 99%
“…[22] A new doping approach of small conjugated molecules and polymers by fluorinated alkylsilanes was introduced, however the doping of DA copolymers by fluorinated alkylsilanes has not been reported. [23] PDPP(2-OD) 2 TT is one of the benchmark DA copolymers for transistor applications having a hole mobility in 1-10 cm 2 V −1 s −1 range and a HOMO level of about −5.35 eV. It comprises alternating DPP and thieno [3,2-b]thiophene (TT) moieties and C 20 H 41 -solubilizing alkyl chains (solubilizers) having a branching point on the second carbon atom.…”
Section: Doi: 101002/adma201506295mentioning
confidence: 99%
“…This molecule is reported to yield acid doping of conjugated molecules. 3 We found that the doping process of rr-P3HT with TCFOS is sufficiently slow to measure the doping kinetics. The dopant density is derived from the transfer curves as a function of temperature and exposure time.…”
Section: Doping Kinetics Of Organic Semiconductors Investigated By Fimentioning
confidence: 99%
“…A gas sensor could be envisaged by monitoring the increase in conductance upon exposure to the target analyte. 3 To fabricate a reliable gas sensor it is important to understand the kinetics of the doping process. However, the number of studies on the doping kinetics is limited.…”
Section: Doping Kinetics Of Organic Semiconductors Investigated By Fimentioning
confidence: 99%